Incremental urbanism: characteristics and implications of residential renewal through owner-driven demolition and rebuilding. Issue 3 (May 2015) - Pinnegar, Simon; Randolph, Bill; Freestone, Robert
<x content-type="archive" xml:space="preserve">Abstract</x> Much contemporary reworking of suburban form takes place both beyond the gaze of urban theory and outside the regulatory ambit of planning systems. An increasingly significant phenomenon in many low density cities dominated by private property markets that has fallen under the radar in these terms is the owner-led incremental demolition and rebuilding of residential dwellings on a one-for-one basis. This paper examines the nature, process, policy aspects and conceptual implications of this process in an Australian setting. It first establishes the scale of the so-called 'knockdown rebuild' phenomenon in Sydney, its major drivers, direct impacts and international referents. This depiction then establishes a platform for exploring three fundamental questions or 'fissures' in regard to the targets and modus operandi of strategic planning, the implementation of statutory planning at the micro-scale, and the complex interplay between individual household actions and the broader political economy in contemporary conceptualisations of suburban change.